AMINO ACID AND FATTY ACID COMPOSITION OF ETHIOPIAN TARO - Temesgen, Melese; Retta, Negussie; Tesfaye, Etalem (American Journal of Food Sciences and Nutrition, 2017)
The purpose of this study was designed to investigate the amino acid and fatty acid composition of taro leaf and corm samples. An UHPLC and GC-FID method was used for the determination of amino acids and fatty acid composition, respectively. Taro leaf was processed as a powder and pre-curd concentrates while the corm was pre-gelatinized with and without peel prior to the analysis. The amino acid and fatty acid composition (%) of the analyzed samples were quantified with their relative area comparing with respective standards. In the present study, the leaf and corm of taro contained the three essential amino acids leucine, lysine and methionine. For the study, the calculated amino acid values were low in corm samples, but amino acid composition was higher in the leaf samples. Concerning fatty acids, the dominant fatty acid in the leaf and corm was oleic acid (C18:1, n-9) which ranged from 140.697 ± 0.054 to 216.775 ± 0.043 and 101.932 ± 0.023 to 101.950 ± 0. 04 mg/100 g, respectively. In the study, the fatty acid compositions in leaf were higher than the corm. This means that taro leaf would be considered as a good source of essential amino acid and fatty acid than the corm. Finally, from the proportion (mg/100 g) of saturated, monounsaturated and polyunsaturated fatty acids, the unsaturated fatty acids were the predominant fatty acids observed. The presence of high levels of unsaturated fatty acids in the entire investigation of our study taro is nutritionally rich.